A Novel Quasi-Cyclic LDPC Codes Construction Method for High-Speed Parallel Decoding - Zheng, Ya Dan; Wu, Shang Zhu; Xiang, Hai Ge; Wang, Da; Dong, Ming Ke (Applied Mechanics and Materials, 2013)
The decoding parallelism of quasi-cyclic low density parity check (QC-LDPC) codes, an important realization factor of LDPC codes, is limited by the block size. Joint row-column (JRC) decoding algorithm, an efficient decoding technique having low computation cost and small iteration number, also suffers from the decoding parallelism limitation in QC-LDPC application. In this paper, a novel LDPC-code construction method is presented and validated. This method constructs the row sets to eliminate the data access conflicts, and it clearly enhances the decoding parallelism while avoids any degradation of bit error rate (BER) performance.